Camelina Seed and Its Effect on Avian Wildlife Species - Mentnech, Keith J.; Delfelder, C.J.; Seitz, Daniel E.; Beyer, R. Scott (My University, 2016)
In Western Kansas, as water availability decreases, agriculture producers are looking for alternative crops that use less water. Also in western Kansas is our important game bird recreation area. And when we use Camelina (Camelina sativa L. Crantz) seed (CS), due to early harvest, we are interested in what effect these little seeds have on early growth of birds since they will hatch in early spring right at CS harvest. In this study, we used 45 2 week-old Cobb 500 broiler chicks for a 7-day experimental period that were randomly assigned to 15 battery cages, each with 3 chicks, for five feed treatments with a control, a 5% and a 10% whole CS inclusion rate, and a 5% and a 10% ground CS inclusion rate. There were no mortalities throughout the experiment. As a result of the study, there were no statistical differences between the treatments, respectively. In conclusion, the results indicate that Camelina seed, whether whole or ground, will not pose a threat to game bird recreation areas nearby agriculture producers.
Keywords: Fall 2016